INCORPORATION OF SODIUM HYALURONATE AND NYAMPLUNG (Calophylum inophyllum) CAKE EXTRACT TO IMPROVE BIOPLASTIC CHARACTERISTIC : - Rini Umiyati; Chusnul Hidayat; Ria Millati; Teguh Ariyanto (BIOTROPIA, 2022)
The cross-linking agent plays an important role in bioplastic mechanical properties. This study aimed to determine the effect of Sodium Hyaluronate (SoHA) as a synthetic cross-linking agent and the addition of Nyamplung Cake Extract (NCE) as an antimicrobial agent in the manufacture of bioplastic with hydroxypropyl starch (HPS) as based ingredient using the thermo-compression method. The novelty of the study was thiocyanate (SCN) formation in zone 3 (2161.66-2162.02/cm) and cyanate (C-N=O) in zone 6 (1,411.57 - 1,412.61/cm) of (1, 2 and 3%) SoHA bioplastic and cyanate formation in zone 6 and 7 (1,411.37 - 1,558.59/cm) of (1, 2 and 3%) SoHA – 20% NCE combined bioplastic originating from acetanilide group in SoHA and amide group in NCE. The formation of SCN and C-N=O in 2 and 3% SoHA bioplastic improved its sensitivity against gram-positive bacteria (Staphylococcus aureus) indicated by 0.6 mm and 0.45 mm inhibition zone, respectively. C-N=O formed in (1, 2 and 3%) SoHA – 20% NCE combined with bioplastic had 3.25 mm average inhibition zone against gram-positive bacteria (S. aureus), 2.75 mm against gram-negative bacteria (Escherichia coli), and 0.71 mm against fungi (Aspergillus niger). The analysis of mechanical properties showed that an addition of 3% SoHA was able to increase tensile strength and modulus of elasticity while reducing elongation, water solubility and water vapor permeability. Addition of (1, 2 and 3%) SoHA – 20% NCE resulted in a reverse effect.